Effects of vibrations induced by electric tooth brush on amount of canine retraction: a cross sectional study done at University of Lahore - Akbar, Aaisha; Attique Ur Rehman; Fatima, Mariam (Journal of the Pakistan Medical Association, 2022)
Objective: The study was done to evaluate the effect of localized vibration on amount of canine retraction after 1st premolar extractions and to assess the anchorage loss. Subject and methods: This quasi-experimental clinical study was conducted at University College of dentistry, Department of Orthodontics, University of Lahore. Data was collected from 30 patients who were already undergoing orthodontic treatment after taking their consent. The study was completed in one year, from Jan 2019 to Feb 2020. Results were compared with independent samples t-test using IBM-SPSS version 23.0. Results: There was no statistically significant difference in the amount of tooth movement between the experimental and control side (P = 0.22). There was also no significant difference in the loss of anchorage (in terms of mesial movement of molar and rotation of canine) between both the groups (P > 0.05). Patients reported the use of electric tooth brush very practical and comfortable. No harm was observed. Conclusion: Supplemental vibrations induced by electric tooth brush did not increase the amount of tooth movement in terms of canine retraction nor did it decrease the loss of anchorage. Key words: Accelerated tooth movement, light force, tooth vibration.